Development of a portable heavy-water leak sensor based on laser absorption spectroscopy. (January 2016) - Lee, Lim; Park, Hyunmin; Kim, Taek-Soo; Kim, Minho; Jeong, Do-Young
Highlights: We developed a compact and portable laser sensor for a detection of heavy water leakage. The sensor is wearable and also easy to use to search for the leak point. It is sensitive enough to find invisible very tiny leaks. Abstract: A compact and portable leak sensor based on cavity enhanced absorption spectroscopy has been newly developed for a detection of heavy water leakage which may happen in the facilities using heavy water such as pressurized heavy water reactor (PHWR). The developed portable sensor is suitable as an individual instrument for the measuring leak rate and finding the leak location because it is sufficiently compact in size and weight and operated by using an internal battery. In the performance test, the minimum detectable leak rate was estimated as 0.05 g/day from the calibration curve. This new sensor is expected to be a reliable and promising device for the detection of heavy water leakage since it has advantages on real-time monitoring and early detection for nuclear safety.